Oxidative stress response: a critical factor affecting the ecological competitiveness of Streptococcus mutans - Xingqun Cheng; Xin Xu; Xuedong Zhou; Jia Ning (Journal of Oral Microbiology)
Oral microecological balance is closely associated with the development of dental caries. Oxidative stress is one of the important factors regulating the composition and structure of the oral microbial community. Streptococcus mutans is linked to the occurrence and development of dental caries. The ability of S. mutans to withstand oxidative stress affects its survival competitiveness in biofilms. The oxidative stress regulatory mechanisms of S. mutans include synthesis of reductase, regulation of metal ions uptake, regulator PerR, transcription regulator Spx, extracellular uptake of glutathione, and other related signal transduction systems. Here, we provide an overview of how S. mutans adapts to oxidative stress and its influence on oral microecology, which may offer novel options to investigate the cariogenic mechanisms of S. mutans in the oral microenvironment, and new targets for the ecological prevention and treatment of dental caries.